Perihal yang Perlu Ditingkatkan pada Pasar Malam di Denpasar, Studi Kasus: Pasar Malam Kreneng - I Wayan Dedek Surya Mahadipa; Made Anggita Wahyudi Linggasani; Ni Luh Anik Puspa Ningsih (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2023)
The night market is a place for recreation and buying and selling transactions for the community. Night market visitors have a very wide range of diversity (gender, age, social and economic strata, and etc). The night market has many advantages besides being able to attract a variety of visitors. But on the one hand, the night market is also inseparable from its shortcomings. Among them are cleanliness, sanitation, material sustainability on attraction rides and night market buildings. The night market also has the potential as a space to gather many people in one place so it is right to be used as a place to promote local products, as well as become a tourism object for the surrounding community. The night market has a moving nature that makes the night market use temporary buildings or temporary architecture. In this case, the night market can be a space for exploration of how the night market can develop temporary architecture to the stage of material sustainability and the optimal and practical use of structures. The night market can also be a space to explore how local architecture can be modified and further developed as a display skin on the night market. So that the night market will feel familiar to visitors who come and can be a special attraction for the night market. In this paper, the author wants to provide solutions to the shortcomings of the night market and provide alternative choices of architectural styles used in the night market. The research steps used in data collection include: input stage (determination of title); process stage (literature review, questionnaire, observation); stage (Process of data analysis, discussion, and conclusion).